Handbook of models for human aging - Conn, P. Michael (Elsevier Academic Press, 2006)
This Handbook is designed as the only comprehensive work available that covers the diversity of aging models currently available. For each animal model, it presents key aspects of biology, nutrition, factors affecting life span, methods of age determination, use in research, and disadvantages/advantes of use. Chapters on comparative models take a broad sweep of age-related diseases, from Alzheimer's to joint disease, cataracts, cancer, and obesity. In addition, there is an historical overview and discussion of model availability, key methods, and ethical issues. *Utilizes a multidisciplinary approach *Shows tricks and approaches not available in primary publications *First volume of its kind to combine both methods of study for human aging and animal models *Over 200 illustrations.